Superwettability of Gas Bubbles and Its Application From Bioinspiration to Advanced Materials - Yu, Cunming (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.